The USSR in the Policy of the Government and President Wojciech Jaruzelski in 1989–1990 (Economic and Political Thought, 2019)
The article shows the attempts to overthrow the USSR’s hegemonyover Poland of the Solidarity camp which on 4 June 1989 won the first freepost-war parliamentary elections in Poland. The author presents views andintentions of communists removed from power as a result of the electionsfrom the camp of which the then Polish president, Wojciech Jaruzelski, camefrom. The amended constitution of the People’s Republic of Poland equippedthe president with enormous competences. The article reports the historyof the president-communist in times of nascent democracy in Poland andhis relations with the USSR, who, however, did not take any steps to hinderPoland’s accession to the European Union and NATO. The study argues withthe thesis that the government pursued the policy of Finlandisation.The author reached for the files from the Presidential Archives and thePPR Historical Records Archive Foundation, not used so far in analyses ofinternational relations.
Keywords: Polish-Soviet relations, Wojciech Jaruzelski, Tadeusz Mazowiecki, Krzysztof Skubiszewski, Warsaw Pact, Comecon, The Council for Mutual Economic Assistance, withdrawal of Soviet troops from Poland, Polish-Soviet disputes over history